Correlation between adenoid nasopharyngeal ratio and tympanometric findings in children with obstructive adenoid enlargement in JOS University Teaching Hospital, Nigeria - Turaki, Ishaku; Benjamin, Bako Babson; Jimlin, Mgbachi Chukwunonso; Ma'an, Nuhu Danle; Kokong, Daniel Damasau; Tonga, Nimkur Lohpon (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Adenoid enlargement plays a significant role in the pathogenesis of otitis media with effusion (OME). Adenoid nasopharyngeal ratio (ANR) of 0.67 was used as an indication for Adenoidectomy in children with obstructive adenotonsillar enlargement. OME is the commonest cause of reversible hearing loss in children. Tympanometry is an objective way the diagnosing OME. This study aimed to evaluate the correlation between ANR and tympanometry findings. Methods: This study was a prospective cohort Hospital-based study conducted at Jos University Teaching Hospital, Nigeria between 5th of August 2020 to 5th of July, 2021. Ethical clearance was obtained. Participants had digital X-Ray postnasal space done and ANR calculated using Fujioka et al, method and subsequently had Tympanometry done and findings analysed using SPSS Version 26.0. Results: A total of 95 patients were evaluated, 78.9% were in the age group of 2-5 years followed by 6-9 years (15.8%). There were 58(61.1%) males and 37(38.9%) females, with a M: F=1.6:1. ANR Mean was 0.76 and SD of ±0.17. Grading of the adenoids using Fujioka et al method showed 45 (47.4%) patients having grade 2 Adenoids and 50 (52.6%) patients having grade 3. Prevalence of type A, B and C tympanograms were 36.8%, 24.7% and 38.4% respectively. Strong Correlation between ANR and tympanometric findings was noted with a p value of<0.001 and correlation coefficient (r) value of 683. Conclusions: This study showed strong correlation between ANR and tympanometric findings evidenced by high prevalence of types B and C tympanograms in patients with adenoid enlargement.